Islamic Bioethics from the Perspective of Islamic Religious Education toward the Development of Modern Science - Muhammad Fauzi Noor; Ani Cahyadi; Fahmi Hamdi; Salamah Salamah (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
The rapid development of modern science and technology, particularly in the fields of medicine, biotechnology, and healthcare, has significantly transformed human life. Innovations such as genetic engineering, cloning, in vitro fertilization (IVF), organ transplantation, and vaccine development have contributed greatly to improving human health and quality of life. However, these advancements also raise ethical, moral, and religious concerns that require comprehensive analysis, particularly from the perspective of Islamic bioethics. This study aims to analyze the role of Islamic bioethics and Islamic Religious Education in addressing the challenges posed by modern scientific development. The research employs a qualitative approach using library research methods by examining books, scientific journals, fatwas, and other relevant academic literature related to Islamic bioethics, maqashid sharia, and the ethics of modern science. The findings indicate that Islam fundamentally supports scientific and technological advancement as long as it remains aligned with moral values and the objectives of Islamic law (maqashid sharia). Islamic bioethics functions as an ethical framework for evaluating modern biomedical technologies by emphasizing the protection of religion, life, intellect, lineage, and property. Furthermore, Islamic Religious Education plays a strategic role in fostering ethical awareness, critical thinking, and spiritual responsibility among students in responding to technological advancement. Therefore, the integration of Islamic bioethics into Islamic Religious Education is essential for developing a generation that is intellectually competent, morally responsible, and spiritually grounded in facing the challenges of modern science and technology.